Acid resistance of OPS lightweight concrete with unground POFA as partial fine aggregate replacement - Mohd Hanafi, Hashim; Khairunisa, Muthusamy; Saffuan, Wan Ahmad (Universiti Malaysia Pahang, 2018)
Oil palm shell (OPS) and Palm oil fuel ash (POFA) is a waste material generated in palm oil mill. This waste material generally dumping at open field area causing health hazards and environmental pollution problems. Due to its abundance and characteristics, many researchers have evaluated its potential as a construction material. The objective of this research is investigating the effect of unground palm oil fuel ash (POFA) content as partial fine aggregate replacement towards durability of oil palm shell lightweight aggregate concrete in acidic environment. Five types of mixes consisting 0%, 5%, 10%, 15% and 20% unground POFA as partial fine aggregate replacement were prepared in form of cubes were used for this research. After the specimens were water cured for 28 days before immersed in hydrochloric acid solution for 1800hr. The durability of specimens was evaluated by measuring the weight loss and compressive strength at end of testing period. The result shows that specimen containing 10% unground POFA experience the least mass loss of all. Utilization of unground POFA at suitable amount enhances the concrete durability through filler effect that promotes the densification of concrete internal structure. However, use of unground POFA beyond the optimum amount causes the concrete to experience higher mass loss and higher deterioration.